Absorptive capacity impact on the relationship between foreign direct investment and economic growth in Malaysia - Aziz, Nusra Izzaty (2022)
The nexus between FDI and economic growth have been debated widely by many scholars. There are lots of different perceptions between FDI and GDP. Though the relationship is proved to be different, it depends on the absorptive capacity of the host country. For the host country to exploit spillovers from FDI, it needs to have a minimum amount of absorptive capacity. Therefore, in this thesis, the relationship between FDI and GDP in Malaysia was first investigated. Then, absorptive capacity, which is only limited to human capital, financial development, and trade openness, was included in the relationship between FDI and economic growth to determine the effectiveness of absorptive capacity towards the relationship between FDI and economic growth in Malaysia. The data was collected from World Development Indicator (WDI) from the duration of 1975 to 2019. In order to analyse the relationship between FDI and economic growth with the presence of absorptive capacity in Malaysia, Automated Regression Distributed Lag (ARDL) techniques were adopted to obtain the results. Firstly, preliminary analysis was taken to avoid spurious regression. The first stage analysis included is Augmented Dickey-Fuller, and Phillips Perron unit root test analysis was conducted to determine the stationarity of the variables. Then, ARDL cointegration bounds testing determined the cointegration of each model. Based on the results, short-run and long-run analysis were tested by using ARDL and Error Correction Models (ECM). By analysing the analysis in Stata 16 software, the unit root test results show that all the variables are stationary but at a different level of stationarity. Thus, ARDL bounds testing was tested to test the presence of cointegration in the models. The results show that there is cointegration in all models. The direct impact of FDI towards growth only shows a short-run relationship. Meanwhile, when human capital, financial development, and trade openness are the moderating factors, all of the models show a positive relationship for both the long and short run. Apparently, by the presence of absorptive capacity, the results of FDI and economic growth relationship showing only short-run effect. These results proved that absorptive capacity impact on the relationship between FDI and economic growth in Malaysia could only be determined in the short run. Also, the diagnostic test shows no autocorrelation and heteroskedasticity in the models. CUSUMSQ test signifies the specification of the model.